Pro C♯ 5.0 and the .NET 4.5 framework - Troelsen, Andrew W. (Apress, 2012)
This new edition of Pro C♯ 5.0 and the .NET 4.5 Platform has been completely revised and rewritten to reflect the latest changes to the C♯ language specification and new advances in the .NET Framework. You'll find new chapters covering all the important new features that make .NET 4.5 the most comprehensive release yet, including: .NET APIs for Windows 8 style UI apps New asynchronous task-based model for async operations How HTML5 support is being wrapped into C♯ web applications New programming interfaces for HTTP applications, including improved IPv6 support Expanded WPF, WCF and WF libraries giving C♯ more power than ever before This comes on top of award winning coverage of core C♯ features, both old and new, that have made the previous editions of this book so popular (you'll find everything from generics to pLINQ covered here). The mission of this text is to provide you with a rock-solid foundation in the C♯ programming language and the core aspects of the .NET platform (assemblies, remoting, Windows Forms, Web Forms, ADO.NET, XML web services, etc.). Once you digest the information presented in these 25 chapters, you'll be in a perfect position to apply this knowledge to your specific programming assignments, and you'll be well equipped to explore the .NET universe on your own terms.
Print version record
Keywords: Microsoft .NET Framework; C# (Computer program language); Internet programming; C# (Langage de programmation); Programmation Internet; Informatique